2019
DOI: 10.1038/s41561-019-0389-4
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation by aerosols from anthropogenic pollution

Abstract: The formation of ice particles in the atmosphere strongly affects cloud properties and the climate. While mineral dust is known to be an effective ice nucleating particle, the role of aerosols from anthropogenic pollution in ice nucleation is still under debate. Here we probe the ice nucleation ability of different aerosol types by combining 11-year observations from multiple satellites and cloud-resolving model simulations. We find that, for strong convective systems, ice particle effective radius near cloud … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 71 publications
4
48
1
Order By: Relevance
“…The results further support our explanation that the different w in Cu and Sc, which governs the responses of S eff to aerosols, could be the underlying cause for the distinct AIE. Previous studies on ice clouds also revealed that the convection strength and water vapor could modulate the opposite AIE (Zhao, Liou, et al, 2018;Zhao et al, 2019) but the present study focuses on warm clouds with a different underlying mechanism.…”
Section: Aerosol Effects On Cloud Supersaturationmentioning
confidence: 90%
“…The results further support our explanation that the different w in Cu and Sc, which governs the responses of S eff to aerosols, could be the underlying cause for the distinct AIE. Previous studies on ice clouds also revealed that the convection strength and water vapor could modulate the opposite AIE (Zhao, Liou, et al, 2018;Zhao et al, 2019) but the present study focuses on warm clouds with a different underlying mechanism.…”
Section: Aerosol Effects On Cloud Supersaturationmentioning
confidence: 90%
“…We understand the uncertainties and caveats associated with using MODIS AOD data, but it is the only aerosol dataset available for such a long time period and over a large region, and it has been used for numerous observational studies in studying aerosol effects (e.g., Koren et al 2010;Peng et al 2016;Jiang et al 2018;Zhao et al 2019). Statistical significance of the correlation between AOD and hail occurrence is determined from 10 000 bootstrapped resamples.…”
Section: B Meteorological Datamentioning
confidence: 99%
“…If the partial correlations are similar to the corresponding total correlation, the meteorological parameters would have little effect on the total correlation. This technique was used to look at covariations of meteorological parameters with aerosols in a few previous studies (Zhao et al 2018(Zhao et al , 2019. The partial correlation calculations are conducted with nine meteorological parameters shown in Table 3 (top) eliminated individually and simultaneously.…”
Section: ) Correlation With Aerosol Loadingmentioning
confidence: 99%
“…Tobo et al (2019) recently reported that dust and biological material from glacial valleys in Svalbard may be an important source of INPs in the region. We also note that we sampled while the Oden was moored in the port of Longyearbyen where local pollution sources may have been significant (Zhao et al, 2019).…”
Section: 5mentioning
confidence: 99%